Analisis Pengaruh Flash Sale, Tagline “Gratis Ongkir” Dan Layanan Cash On Delivery Terhadap Keputusan Pembelian Pada Marketplace Shopee - Appuliani, Ani; Handayani, Langgeng Sri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The rapid development of digital technology has driven the growth of the internet and given rise to online shopping platforms such as Shopee. Shopee offers convenience in buying and selling transactions and various online services, which can accelerate economic growth globally. This study aims to determine the influence of the Flash Sale program, the “Free Shipping” Tagline, and the Cash on Delivery (COD) Service on purchasing decisions in the Shopee marketplace. This study uses a quantitative method with a non-probability sampling technique, namely judgment sampling. The research sample consisted of 120 people who lived in Sukamahi Village and had experience shopping online through the Shopee application at least 3 times. The data analysis technique used multiple linear regression analysis using IBM SPSS 23. The results of the study show that the Flash Sale program, the “Free Shipping” Tagline, and the Cash on Delivery (COD) Service have a positive and significant influence on purchasing decisions in the Shopee marketplace. The R-Square value of 0.622 indicates that 62.2% of the variation in purchase decision value is determined by the role of the Flash Sale variable, the “Free Shipping” Tagline, and the Cash on Delivery (COD) Service, while the remaining 37.8% is influenced by other variables outside of the study. Thus, the Flash Sale program, the “Free Shipping” Tagline, and the Cash on Delivery (COD) Service are proven to have a positive influence on purchasing decisions in the Shopee marketplace. This indicates that Shopee needs to continue to maintain and improve these programs to increase sales and customer satisfaction.